The influence of vinegars on exposure of dentinal tubules: a SEM evaluation. - Zandim-Barcelos, Daniela Leal [UNESP]; Corrêa, Fernanda Oliveira Bello; Sampaio, José Eduardo Cezar [UNESP]; Rossa Júnior, Carlos [UNESP] (FapUNIFESP (SciELO), 2004)
Dentin hypersensitivity is a common painful condition observed in clinics. Dietary habits have been much associated with its development and persistence during and following periodontal treatment. The aim of this in vitro study was to evaluate the influence of vinegars on the removal of smear layer and exposure of dentinal tubules. Extracted human teeth were submitted to manual scaling with Gracey curettes in order to remove the cementum as well as to form a smear layer. Dentin samples with 3 mm(2) were obtained and distributed into six experimental groups: one control and five types of vinegars (alcohol, apple, rice, white wine and balsamic). Each group included two methods of vinegar application: topical and friction. After routine preparation for SEM analysis, photomicrographs were assessed by a calibrated and blind examiner using an appropriate index system. Kruskal-Wallis test indicated a significant influence of vinegars on smear layer removal. There was a statistically significant difference between groups treated with apple, white and rice vinegars and the control group (p < 0.05). Nevertheless, Mann-Whitney test indicated that removal of smear layer did not vary with the method of application (topical versus friction) for any of the tested substances. We can conclude that the contact of vinegar may remove smear layer and expose dentinal tubules, regardless of the type of application. However, balsamic vinegar was associated with less removal of smear layer after both methods of application.
Keywords: acetic acid; biomedical and dental materials; dental surgery; dentin; dentin sensitivity; diet; drug effect; endodontics; human; in vitro study; nonparametric test; scanning electron microscopy; tooth pulp; ultrastructure; Acetic Acid; Dental Pulp Cavity; Dentin; Dentin Sensitivity; Diet; Humans; Microscopy, Electron, Scanning; Root Canal Irrigants; Root Canal Preparation; Smear Layer; Statistics, Nonparametric